Trade in the time of parcels - López González, Javier (OECD Publishing, 2021)
Today, more parcels are crossing international borders than ever before. While this has given rise to new opportunities, not least for individuals and SMEs who are now more directly engaged in trade, it is also raising new challenges. This paper explores this complex and evolving environment, identifying the types of goods that are traded as parcels and the different actors along the parcels supply chain, as well as the policies to help ensure that parcels get to where they are needed. Empirical analysis shows that progress on digital connectivity and trade facilitation measures, such as increased transparency or automating border processes, are likely to have a greater trade-enhancing impact on parcel trade than on "traditional" trade. In contrast, greater differences in regulations across countries in transportation, courier or logistics services are associated with lower trade in parcels. Overall, enabling benefits from trade in parcels and facing forthcoming challenges requires a comprehensive policy approach across a number of areas and throughout the parcel supply chain
Keywords: Trade